Using Polyacrylamide Hydrogels to Model Physiological Aortic Stiffness Reveals that Microtubules Are Critical Regulators of Isolated Smooth Muscle Cell Morphology and Contractility - Ahmed, Sultan; Johnson, Robert. T.; Solanki, Reesha; Afewerki, Teclino; Wostear, Finn; Warren, Derek. T. (Frontiers in Pharmacology, 2022)
Vascular smooth muscle cells (VSMCs) are the predominant cell type in the medial layer of the aortic wall and normally exist in a quiescent, contractile phenotype where actomyosin-derived contractile forces maintain vascular tone. However, VSMCs are not terminally differentiated and can dedifferentiate into a proliferative, synthetic phenotype. Actomyosin force generation is essential for the function of both phenotypes. Whilst much is already known about the mechanisms of VSMC actomyosin force generation, existing assays are either low throughput and time consuming, or qualitative and inconsistent. In this study, we use polyacrylamide hydrogels, tuned to mimic the physiological stiffness of the aortic wall, in a VSMC contractility assay. Isolated VSMC area decreases following stimulation with the contractile agonists angiotensin II or carbachol. Importantly, the angiotensin II induced reduction in cell area correlated with increased traction stress generation. Inhibition of actomyosin activity using blebbistatin or Y-27632 prevented angiotensin II mediated changes in VSMC morphology, suggesting that changes in VSMC morphology and actomyosin activity are core components of the contractile response. Furthermore, we show that microtubule stability is an essential regulator of isolated VSMC contractility. Treatment with either colchicine or paclitaxel uncoupled the morphological and/or traction stress responses of angiotensin II stimulated VSMCs. Our findings support the tensegrity model of cellular mechanics and we demonstrate that microtubules act to balance actomyosin-derived traction stress generation and regulate the morphological responses of VSMCs.